Pengaruh Shading Eggcrate dan Pengunaan Kaca Panasap Guna Efesiensi Energi yang di Ukur dengan Nilai OTTV Bangunan Bertingkat Studi Kasus : Brilian Tower - Gilang Pratama; Johanita Anggia Rini; Isyrin Yus Fauziah (International Forum of Researchers and Lecturers, 2025)
The energy crisis and global warming are driving the importance of energy efficiency in building design. An ideal building not only prioritizes aesthetics and function, but also energy efficiency as well as comfort and safety for its occupants. In Indonesia, the Green Building Council Indonesia (GBCI) plays a role in promoting environmentally friendly and sustainable architectural practices. One popular method for energy efficiency is the use of eggcrate, which is a shading system in the form of lattices that reduces the intensity of sunlight, thereby lowering indoor temperatures and reducing energy use for cooling. The use of heat-reflective glass is also common in energy-efficient building design, because it reflects solar radiation and reduces incoming heat without sacrificing natural light. This reduces the workload of the air conditioning system, thereby increasing energy efficiency. According to Asih (2012), environmental control in buildings is greatly influenced by the use of glass and shading elements. Building façades, including glass areas, play an important role in energy conservation by reducing incoming heat conduction. In addition, glass also influences natural lighting and has positive psychological effects, while maintaining comfort and energy efficiency in buildings.